Manufacturer-supplier relationships : An empirical study of German manufacturing companies - Szwejczewski, Marek; Lemke, Fred; Goffin, Keith (Emerald Group Publishing Limited, 2005)
Effective management of suppliers is one of the ways manufacturing companies can improve their performance. Typically, it has been argued in the literature that close relationships with suppliers should be developed, in contrast to the traditional price-driven transactional relationships. However, there has been relatively little empirical research on how supplier management is applied.
Keywords: Buyer-seller relationships; Germany; Manufacturing industries; Supply chain management